2023
DOI: 10.1117/1.jmi.10.s1.s11903
|View full text |Cite
|
Sign up to set email alerts
|

E pluribus unum: prospective acceptability benchmarking from the Contouring Collaborative for Consensus in Radiation Oncology crowdsourced initiative for multiobserver segmentation

Abstract: . Purpose Contouring Collaborative for Consensus in Radiation Oncology (C3RO) is a crowdsourced challenge engaging radiation oncologists across various expertise levels in segmentation. An obstacle to artificial intelligence (AI) development is the paucity of multiexpert datasets; consequently, we sought to characterize whether aggregate segmentations generated from multiple nonexperts could meet or exceed recognized expert agreement. Approach Participants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The current standard of care for OPC RT relies on manually generated segmentation of the primary gross tumor volume (GTVp) by clinical experts as a target structure to deliver RT dose. However, the GTVp in OPC is notorious for being one of the most difficult structures amongst all cancer types to perform accurate segmentation for RT planning due to its exceptionally high interobserver variability 2–4 . Subsequently, GTVp segmentation has been cited as the single largest factor of uncertainty in RT planning 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The current standard of care for OPC RT relies on manually generated segmentation of the primary gross tumor volume (GTVp) by clinical experts as a target structure to deliver RT dose. However, the GTVp in OPC is notorious for being one of the most difficult structures amongst all cancer types to perform accurate segmentation for RT planning due to its exceptionally high interobserver variability 2–4 . Subsequently, GTVp segmentation has been cited as the single largest factor of uncertainty in RT planning 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, stratification of evaluation metrics, as we have performed in our study, allows for ROI-specific thresholds that act as rough measures of clinical acceptability. Notably, our ROI-specific thresholds are derived from "gold standard" measurements provided by recognized experts within particular disease sites, which were established to have significantly improved segmentation consistency compared to non-experts in previous work 3 . When stratified by previously defined expert IOV cutoffs, the ROIs with the lowest percentage of observers that were able to cross cutoffs were often tumor volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The number of experts used to derive the consensus segmentation was variable depending on the ROI; more information can be found in the corresponding data descriptor 7 . Though “experts” were subjectively determined in the original C3RO study, they demonstrated significantly improved interobserver variability compared to non-expert counterparts 3 . Therefore, the expert STAPLE can be considered as a “gold standard” segmentation to be used for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific patient cases were selected by C3RO collaborators on the basis of being adequate reflections of routine patients a generalist radiation oncologist may see in a typical workflow (i.e., not overly complex). Further details on the study design for C3RO can be found in Lin & Wahid et al 19 . www.nature.com/scientificdata www.nature.com/scientificdata/ Imaging protocols.…”
Section: Methodsmentioning
confidence: 99%